2017
DOI: 10.1007/s11701-017-0742-9
|View full text |Cite
|
Sign up to set email alerts
|

Robotic repair of symptomatic Spigelian hernias: a series of three cases and surgical technique review

Abstract: Spigelian hernias are a rare defect in the Spigelian aponeurosis, comprising of 0.1-2% of all hernias. These rare hernias can contain intra-abdominal tissue, and rarely bladder. Spigelian hernias pose a high risk for incarceration or strangulation of its herniated content if not repaired promptly. There are a number of routinely employed operative techniques to repair Spigelian hernias, including open or laparoscopic, suture or mesh repair, transabdominal pre-peritoneal approach or totally extraperitoneal appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
0
19
0
4
Order By: Relevance
“…It has been reported that the long-term recurrence rate may be lower with mesh than with simple suture closure [ 9 ]. In recent years, laparoscopic surgery including robotic surgery has been increasingly used in reported cases of Spigelian hernia [ [13] , [14] , [15] , [16] , [17] ]. In the present study, we did not use the inexpensive transabdominal preperitoneal approach (TAPP) method, but rather the IPOM method, which we usually use for abdominal wall scar hernias at our hospital, in case 1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the long-term recurrence rate may be lower with mesh than with simple suture closure [ 9 ]. In recent years, laparoscopic surgery including robotic surgery has been increasingly used in reported cases of Spigelian hernia [ [13] , [14] , [15] , [16] , [17] ]. In the present study, we did not use the inexpensive transabdominal preperitoneal approach (TAPP) method, but rather the IPOM method, which we usually use for abdominal wall scar hernias at our hospital, in case 1.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported minimal pain and hospitalization was no longer than overnight admission. 10 Follow up, regarding the recurrence rate, for these three cases was not reported. Pirolla et al compared two cases of robotic repair to three cases of laparoscopic spigelian hernia repair.…”
Section: Discussionmentioning
confidence: 95%
“…Most commonly, contents of the hernia include omentum or intestine; others, however, contain ovary, fallopian tube, uterus, testis, gallbladder, stomach, Meckel's diverticulum, appendix, and bladder. 8,10…”
Section: Discussionmentioning
confidence: 99%
“…Todas las opciones presentan buenos resultados clínicos, pero aún no contamos con estudios que puedan sacar conclusiones definitivas sobre cuál es la mejor técnica de abordaje, principalmente por la rareza de este proceso y por la falta de revisiones sistemáticas, excluyendo los trabajos publicados por Moreno-Egea, único estudio aleatorizado existente hasta la fecha 7,9,11 . Sobre la posibilidad de emplear el acceso por robótica, apenas hay documentación, aunque parece que podría tener algo de ventaja en el periodo de recuperación más corto y en una mayor precisión durante la técnica con menor riesgo de sangrado 12 , aunque todavía no pueda concluirse nada.…”
Section: Discussionunclassified